Analyzing cultural tourism promotion on Instagram: a cross-cultural perspective. Issue 3 (24th March 2021) - Mele, Emanuele; Kerkhof, Peter; Cantoni, Lorenzo
ABSTRACT: A lack of cross-cultural research has been identified regarding cultural tourism promotion on social media. Using the dimensions of Collectivism-Individualism, Power Distance, and High-Context vs. Low-Context communication, we content analyze cultural value differences in Instagram posts promoting cultural tourism – published by the national tourism organizations of Chile, Portugal, USA, and Netherlands. In addition, an automated content analysis is conducted using the software LIWC2015 to examine linguistic differences between collectivist and individualist destinations' posts. Findings show that cultural tourism promotion on Instagram differs across cultures, highlighting the importance of adapting online content when addressing culturally distant markets.